Analisis Kebutuhan Pengembangan LKPD Berbasis Kearifan Lokal Daerah Banyuwangi di Sekolah Dasar - Chumi Zahroul Fitriyah; Rizki Putri Wardani (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2022)
LKPD is one of the learning materials developed by the teacher. Integrating  LKPD with local wisdom can lead the students to learn well while at the same time know about Banyuwangi local wisdoms. There are so many kinds of Banyuwangi local wisdoms, among others, Batik Blambangan, Tumpeng Sewu Tradition, Barong Ider, Barong Kemiren, and Endhog endhogantradition. Banyuwangi,  located in the east of Java island, is known as “The Sunrise of Java” due to the sun rising firstly in this region. Besides, Banyuwangi is also famous as the Using Region that has unique local wisdoms. The objective of this study is to describe a preliminary study about local wisdom LKPD in the Bayuwangi region, including curriculum analysis, integrating local wisdom by theme mapping, and deciding lessons based on the basic competence and indicator. The study uses descriptive qualitative  with teachers in Banyuwangi as the research subjects selected using purposive sampling technique. Moreover, the data collection used observation, documentation, and interview. The study was started by doing a preliminary study with curriculum analyses related to LKPD, mapping materials, determining LKPD, and making LKPD. Based on observation, LKPD made by the teachers were not linked to local wisdom. Therefore, improvement is needed to develop LKPD based on Banyuwangi local wisdoms. In addition, local wisdom LKPD can help students to know the value of local wisdoms in the LKPD integrated with the lessons. In the end, it is expected that there will be LKPD developed by the teachers by incorporating local wisdoms